The influence of gut microbiota in cardiovascular diseases - a brief review - Almeida, Cátia (2021)
Lately, the gut microbiota has emerged as an important mediator of the development and the outcomes of certain diseases. It's well known that the gut microbiota plays an important role in maintaining human health. Still far from being completely understood and analyzed is the complexity of this ecosystem, although a close relationship between the gut microbiota and cardiovascular diseases (CVD) has been established. A loss of diversity in the microbiota will lead to physiological changes, which can improve inflammatory or infection states like atherosclerosis and hypertension, the basic pathological process of CVD. Targeting the gut microbiota and its metabolites are new and promising strategies for the treatment and prognosis of CVD.